The role of the teacher in the educational achievement of Roma children - Elekes, Györgyi (Gyermeknevelés Tudományos Folyóirat, 2022)
This paper discusses the role of the teacher as the one who has the most profound influence on school mobility. My analysis draws attention to the teacher, who can facilitate the performance of Roma children at school by fostering a positive attitude toward learning, encouraging positive relationships, and thereby supporting the overall social mobility of this disadvantaged minority group. The research underlying this particular study consists of analyses of the life stories of Roma individuals who hold or about to obtain university degrees and have been particularly successful in the mobility channel of the education system by the standards of the Roma community. I point to the social factors that help or hinder the progress of the individual. In the analysis, particular attention was paid to the microsocial relationships affecting the school performance of Roma students as well as to the question of secondary socialisation.